Prevalence of menstrual pain and symptoms and their association with age and BMI among Japanese female app users - Shuxian Liu; Daisuke Yoneoka; Hitomi Suzuki; Kiriko Sasayama; Eiko Saito; Yuna Naraoka; Momo Hosokawa; Ataru Igarashi; Erika Ota (Scientific Reports)
Abstract Menstruation plays a crucial role in women’s health, with age and BMI potentially influencing menstrual pain and associated symptoms. This cross-sectional study analyzed data from Japanese female Sofy app users aged 12–51 years, collected between March 4, 2021, and August 17, 2023. After excluding duplicate and incomplete responses, as well as participants using contraceptives or painkillers, a total of 32,556 valid responses were included. Among the participants, 66.83% reported experiencing menstrual pain, with 28.33% describing it as mild, 25.13% as moderate, and 13.31% as severe. The average number of symptoms reported was 3.36, including 2.43 physical and 0.82 emotional symptoms. Abdominal pain and depression were the most common physical and emotional symptoms, respectively. Menstrual pain and the number of symptoms exhibited an inverted U-shaped relationship with age, peaking slightly earlier in life, and a U-shaped relationship with BMI. Participants in the normal BMI range reported the lowest prevalence of menstrual pain, while those who were underweight had the highest prevalence. Generalized Additive Models (GAM) revealed significant interactions between age and BMI for both menstrual pain and the number of symptoms (p < 0.0001). These findings revealed the age-related inverted U-shape and BMI-related U-shape patterns across all outcomes. Menstrual pain prevalence peaked around the mid-twenties, and symptoms decreased as BMI approached the normal range. The findings provide valuable insights into identifying high-risk groups and informing the development of targeted interventions to improve women’s health.